Experiences of muslims convert - Norrul Aikma, bt Mohamed (Universiti Malaysia Sarawak (UNIMAS), 2009)
It is in religious conversion context that is as foundational to transform people and each of the great world religions offers a comprehensive conception of the universe, and in so far as such pictures are believed and are built into our dispositional structure, they automatically affect the way in which the believer lives. They determine the overall meaning of life for us. So, it would be nothing short of a miracle if'religion can have profoundly impact on the self-transformation. Therefore, religion is serves as a system for people to find meaning, belonging, identity and selffunctioning in life. This study indicates that there are some factors, cognitive concerns and age-related appeared to have relations with the conversion to Islam and there are some major effects following the conversion to Islam. Moreover, the Muslims convert are said becoming self-actualization.